Development of a low-cost multimodal VR system for engineering design - Roper, Tessa; Lawson, Glyn; Abdullah, Che (2017)
Virtual Reality technologies are available at a lower cost than ever before. However, such systems are developed mainly for the consumer market, and inaccuracies in spatial judgements may make them unsuitable for specific applications like Engineering Design. There is evidence to suggest that the addition of haptic feedback may improve spatial judgements, but most commercially available haptic systems are impractical and unaffordable outside of specialist research settings and large enterprises. We describe the challenges for developing a multimodal VR system using only low-cost off-the-shelf technologies, and demonstrate a working prototype of a system which aims to overcome these issues.